(untitled) (IJAS Indian Journal of African Studies, 2022)
Egypt is constitutionally known as a Republic, however, in practice it is an authoritarian state. The president, as elected head of the state has absolute power to take decisions with regards to administering and running the state. This extends to undermine the provisions created by the constitution for citizens’ rights. As a result, there is little room for any public discourse and civil society activities. This article is an analysis of the civil society growth and prospect under successive regimes in post-colonial Egypt to argue that Egyptian society is largely shaped by the state centric political culture.